Pobyt Adama Mickiewicza w Rosji w świetle Zapisków Ksenofonta Polewoja - Dąbrowska, Magdalena (Acta Polono-Ruthenica, 2019)
This paper presents The Notes (published in Saint Petersburg, 1888) by Xenophon Polevoy (1801–1867), Nikolai’s brother, from a perspective of Adam Mickiewicz’s stay in Russia. It concerns Mickiewicz’s meetings with the Russian poets (A. Pushkin, I. Kozlov and others) in 1825 and 1826, his relations with them and the reception of Crimean Sonnets and Konrad Wallenrod in Russia. Polevoy highly values the Polish poet and considers his contacts with Russians to be friendly. An interpretive background is the periodical “Moskovskij tielegraf”.